(untitled) (El-Wahat Journal for Research and Studies, 2017)
What made me choose this subject the area of research and study, is that I am filled with fear of the dangers that beset the potential destiny of the Arabic language in Algeria. This article aims at clarifying the causes of the decline of Arabic in our social, cultural, economic and even political life. Although it is a national constitutional language, it is revealed to what extent the official and private institutions failed to establish and entrench Arabic in our living reality.. There is no fear indeed since Arabic language as long as it is constitutional language , but this is not enough to justify this lame policy used in dealing with it; if really it is so in the opinion of the whole society and is it truly represents one of the constants of the Algerian state, then we have to abide both officials and citizens. This article attempts to clarify the bet of this honorable language as the language of the Holy Quran, as well as the research into the mechanisms, ways, methods and possible ways to put it on the pedestal it deserves. Keywords - Arabic , Civilization, the culture, legislators, Institutions, the quality.